Bose-Einstein condensates with inhomogeneous scattering length in one and two dimensions - Abdullaev, F. K.; Victo, S.; Gammal, A.; Tomio, L. (Interperiodica, 2005)
We report on investigations of the properties of bright solitons in Bose-Einstein condensates in the presence of point-like spatial inhomogeneities, in one and two dimensions. By considering an analytical variational approach and full numerical simulations, we describe such processes due to interactions between the soliton and the inhomogeneity as the trapping, reflection, and transmission of bright matter solitons. We also study the critical number of particles as a function of the magnitude of the impurity.